Simulation of Braitenberg Method of Differential Wheeled Robot Using Gazebo ROS Features - Bagus, Pradana Bagus Mauludin; Rinanto, Noorman (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2025)
Differential wheeled robots are one type of mobile robot that is easy to design and operate. However, cost limitations and the risk of hardware damage due to collisions when the robot fails to avoid obstacles often become obstacles in direct research on physical devices. To overcome this, this research was conducted in the form of simulations using the Robot Operating System (ROS) and Gazebo. The simulation utilizes the Burger model TurtleBot robot and applies the Braitenberg method as an obstacle avoidance strategy to detect and avoid obstacles in the surrounding environment. The Braitenberg method is an algorithm designed for wheeled vehicles to move automatically by utilizing data from left and right side sensors to control motor rotation. Therefore, it is necessary to test the implementation of this method to ensure that the robot is able to move independently while avoiding obstacles in the vicinity. Keywords: Turtlebot9, ROS, Gazebo, Turtlebot, Braitenberg